Germany's Economic Restart after Covid-19: The Role of Fiscal Policy and Taxation - Clemens Fuest (CESifo Forum, 2021)
Many European economies are gradually recovering from the corona pandemic, although it is not yet over. National governments are using the breather to assess the effectiveness of their less-conventional and short-term crisis-prevention measures. This is important because they must prepare to return to their long-term economic and fiscal priorities. These include strategies to ensure a smooth structural transformation supported by an adequate supply of skilled labor. They are also looking for a plan on what investments they need to undertake in digitization. They also want to answer the question of how they can manage the energy transition and how they can achieve the goals of climate policy. What is needed are financing concepts that keep public debt within reasonable limits and do not place an undue burden on the welfare state. As if that were not enough, the EU member states must simultaneously develop a clear and new vision for the future of the EU and define its role in a globalized world. In doing so, it is important to maintain a balance with national needs and priorities, among others, in recovering from the crisis. This edition of the CESifo Forum offers systematic insights into these critical and urgent policy issues in selected European countries.
Keywords: 330